Clinical evaluation of 3D PEEK implants for skull bone defects repair: a single center case serious - Mohamed Ahmed Elnaggar; Hossam Abdelhakim Elnoamany; Mohamed K. Eissa (Egyptian Journal of Neurosurgery)
Abstract Background Custom-designed 3D-printed polyetheretherketone (PEEK) implants have emerged as a promising option for skull bone defect repair. This study aimed to evaluate the clinical outcomes, feasibility, and safety of using 3D-printed PEEK implants in patients with skull defects. Methods A retrospective case series was conducted at Menoufia University Hospital, reviewing the medical records of patients who underwent cranioplasty between January 2022 and December 2023. Patients aged 18–65 years with skull bone defects due to trauma, surgical resection, or congenital anomalies were included. All patients underwent preoperative CT scans for custom implant design using computer-aided design (CAD) software. The 3D-printed PEEK implants were fabricated and implanted during surgery. Primary outcome measures included successful implant integration and structural stability, while secondary outcomes assessed complications and patient satisfaction. Results Thirteen patients (76.9% male, mean age 45.8 years) were included. The majority of defects were caused by trauma (76.9%). The mean time to cranioplasty was 6 ± 2 months, and the average operative time was 143 ± 34 min. Mean blood loss was 265 ± 97 cc, and the average hospital stay was 2.85 ± 0.9 days. Complications included dural tears in 38.5% of cases, while no immediate postoperative complications were reported. Late complications included one case of convulsions (7.7%) and one superficial infection (7.7%). Radiographic follow-up confirmed successful implant integration in all patients. Conclusion 3D-printed PEEK implants provide a feasible and effective solution for skull bone defect repair, with favorable outcomes and manageable complication rates. These custom implants offer a personalized approach to cranioplasty, but larger studies with longer follow-up are needed to validate these findings.